Rural Land Management Interaction with Urbanization - Delgado-Viñas, Carmen; Gómez-Moreno, María L. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is focuses on how recent urbanization processes modifies the organization and management of the land uses at integrated rural areas in peri-urban and intra-metropolitan areas at local, national, and global levels. The Guest Editors expect that this reprint could serve to provide some answers regarding the impacts of urbanization on rural areas.